Effects of High-Fat Diet on Steatosis, Endoplasmic Reticulum Stress and Autophagy in Liver of Tilapia (Oreochromis niloticus) - Jia, Rui; Cao, Li-Ping; Du, Jin-Liang; He, Qin; Gu, Zheng-Yan; Jeney, Galina; Xu, Pao; Yin, Guo-Jun (Frontiers in Marine Science, 2020)
Hepatic steatosis is the most common phenomenon of lipid metabolism disorder in farmed fish, but its molecular mechanism is poorly understood. Therefore, the present study was aimed to investigate steatosis induced by high-fat diet (HFD) and explore underlying mechanism in tilapia. The fish were fed on control diet or HFD for 90 days. The blood and liver tissues were collected to determine biochemical parameters, genes expression and proteins level after 30, 60 and 90 days and analyzed lipid accumulation, endoplasmic reticulum (ER) stress and autophagy. After 30 days of feeding, the plasma and hepatic lipid content (TG, TCH, LDL-C and HDL-C) and fatty acids (FAs) transportation (fabp1 and CD36) were enhanced significantly in HFD-fed tilapia. After 60 days, the lipid metabolism disorder, such as increase of TG synthesis and free CH formation, and decrease of FAs β-oxidation and biosynthesis, was observed in liver of HFD-fed tilapia. Further, with increasing lipid accumulation, ER stress was induced and worsen hepatic steatosis via activating IRE1 signaling pathway in liver of HFD group after 90 days. Meanwhile, the autophagy was suppressed via impairing AMPK and BFET pathways in HFD-fed tilapia liver after 90 days. Our results demonstrated that HFD feeding induced extensive lipid deposition, promoted ER stress, suppressed autophagy in tilapia liver. Interestingly, these pathological features were positively correlated with the duration of HFD feeding.